Study Deskriptif: Kajian Personal Hygiene Mahasiswa Program Kesehatan untuk Menghadapi Masa Endemi Covid-19 - Nayla Kamilia Fithri; Rizki Amalia; Arga Buntara; Erlina Riyantiasis; Sartika Alifia (Malahayati Nursing Journal, 2023)
ABSTRACT Recently, the government has started calling for the transition to the COVID-19 endemic. The transition to endemic can be implemented if the public is aware and accustomed to independently implementing health protocols for themselves and their families. One of the things that you must get used to is doing good personal hygiene. Adolescents are an age group that is vulnerable to COVID-19 and transmits it to families at home in which there are vulnerable age groups such as the elderly. So it is important to apply personal hygiene practices to adolescents to face the transition period of the COVID-19 endemic. To to find out the personal hygiene practices of health program students during face-to-face lectures at the Universitas Pembangunan Nasional Veteran Jakarta. The type of research used is descriptive analytic with a cross-sectional approach. The research sample amounted to 290  respondents, with the sampling technique carried out by convenience sampling by distributing online questionnaires for 30 days. There were 130 (48.7%) respondents who did not perform hygiene behavior well and 65 (22%) respondents never disinfect masks. Conclusion Most of the health students still do not practice good personal hygiene. The recommendation is to provide input to campusess and the local government to develop policies related to increasing understanding and monitoring in the educational environment in dealing with the learning process with new habits during the COVID-19 period. KeyWord: Students, Personal Hygiene, Survey  ABSTRAK Akhir-akhir ini masa transisi menuju Endemi COVID-19 sudah mulai diserukan oleh pemerintah, transisi menuju endemi dapat diterapkan jika masyarakat sudah dapat menyadari dan membiasakan secara mandiri untuk melakukan protokol kesehatan pada diri dan keluarga. Salah satu yag harus dibiasakan adalah melakukan personal higiene yang baik. Remaja adalah kelompok usia yang rentan untuk terkena COVID-19 dan menularkannya pada keluarga dirumah yang didalamnya ada kelompok usia rentan seperti lansia. Maka penting menerapkan praktik kebersihan diri pada remaja untuk menghadapi masa transisi endemi COVID-19.  Untuk mengetahui praktik personal hygiene  mahasiswa program kesehatan pada masa perkuliahan tatap muka secara langsung di Universitas Pembangunan Nasional Jakarta. jenis penelitian yang digunakan adalah  deskriptif kualitatif dengan pendekatan cross-sectional. Sampel penelitian berjumlah 290 responden, dengan teknik pengambilan sampel dilakukan secara convenience sampling dengan menyebarkan kuesioner secara online selama 30 hari. Penelitian ini menunjukkan bahwa 136 (47%) responden melakukan personal hygeine yang kurang baik dan 65 (22%) responden menjawab tidak mernah mendesinfektan masker sebelum dibuang. Sebagian besar mahasiswa kesehatan masih banyak yang tidak mempraktikan personal hygiene yang baik. Rekomendasinya adalah memberikan masukan kepada kampus dan pemerintah setempat untuk pengembangan kebijakan yang berkaitan dengan peningkatan pemahaman dan monitoring dilingkungan pendidikan dalam menghadapi proses pembelajaran dengan kebiasaan baru pada masa COVID-19. Kata Kunci: Mahasiswa, Kebersihan Individu, Survei